2018
DOI: 10.13080/z-a.2018.105.030
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of field pea with annual legumes for increasing grain yield production

Abstract: In temperate regions, normal-leafed field pea still represents an important crop for grain and animal consumption, even though there is increasing interest in afila type cultivars because of their better standing ability. The effect of dual legume intercropping on grain yield of normal-leafed pea was studied during 2015 and 2016 in order to reduce lodging, to improve grain yield stability and to analyse the competitiveness of field pea with annual legumes and wheat. The research involved six species grown as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It has been reported in many cases that the combination of pea with cereals confers benefits in terms of LER (grain and forage), although it is not always so [12,34]. Combining pea and faba bean is less common, but again, positive and negative effects on yield have been described [35,36]. In our experiments, no grain or biomass yield advantage or disadvantage was found.…”
Section: Discussionmentioning
confidence: 39%
“…It has been reported in many cases that the combination of pea with cereals confers benefits in terms of LER (grain and forage), although it is not always so [12,34]. Combining pea and faba bean is less common, but again, positive and negative effects on yield have been described [35,36]. In our experiments, no grain or biomass yield advantage or disadvantage was found.…”
Section: Discussionmentioning
confidence: 39%
“…Protein content in pea as quoted in literature ranges from 16% to 30.9% [ 6 , 7 ]. In organic production systems in the European Union, peas are considered an important plant species because they are a source of biologically-fixed nitrogen and provide high-quality animal feed that is rich in crude protein and minerals [ 8 ]. Although soybean is one of the primary sources of plant-based protein, the advantages of growing peas over soybeans are its wider geographical area of cultivation and its ability to thrive in colder climates.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean, unlike pea, is one of the significant food allergens [ 9 ]; moreover, the fact that pea grain, unlike soybeans, can be used directly in the diet without prior heat treatment is essential, as this simplifies use and reduces processing costs. Combined sowing of peas with cereals is increasingly used in practice to improve the efficiency of land and water resources, nutrients, and solar radiation [ 8 ]. Furthermore, peas can also be grown as green manure [ 10 ] and as a forage crop, especially in regions where climatic conditions are not favorable for a good seed yield [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that mixing two leaf types had a small or no yield increase compared with two sole leaf monocultures. Živanov et al [42] used a 50:50 SL/L ratio and showed that the yield of the mixture did not differ from the leafed and semi-leafless monocultures, which was intermediate to the monocultures. Antanasovic et al [22] found that a 75:25 SL/L ratio had a greater yield than the monocultures at the 80 plant/m 2 density with 9% and 39% for semi-leafless and leafed monocultures, respectively.…”
Section: Discussionmentioning
confidence: 99%